Transcriptome profiling of male gametophyte development in Nicotiana tabacum - Bokvaj, Pavel; Hafidh, Said; Honys, David (Genomics data, 2015)
Pollen, an extremely reduced bicellular or tricellular male reproductive structure of flowering plants, serves as a model for numerous studies covering wide range of developmental and physiological processes. The pollen development represents a fragile and vital phase of plant ontogenesis and pollen was among the first singular plant tissues thoroughly characterized at the transcriptomic level (Honys and Twell [5]). Arabidopsis pollen developmental transcriptome has been published over a decade ago (Honys and Twell, 2004) and transcriptomes of developing pollen of other species have followed (Rice, Deveshwar et al. [2]; Triticeae, Tran et al. [11]; upland cotton, Ma et al. [8]). However, the transcriptomic data describing the development of tobacco pollen, a bicellular model for cell biology studies, have been missing. Here we provide the transcriptomic data covering three stages (Tupý et al., 1983) of wild type tobacco (Nicotiana tabacum, cv. Samsun) pollen development: uninucleate microspores (UNM, stage 1), early bicellular pollen (eBCP, stage 3) and late bicellular pollen (lBCP, stage 5) as a supplement to the mature pollen (MP), 4 h-pollen tube (PT4), 24 h-pollen tubes (PT24), leaf (LF) and root (RT) transcriptomic data presented in our previous studies (Hafidh et al., 2012a; Hafidh et al., 2012b). We characterized these transcriptomes to refine the knowledge base of male gametophyte-enriched genes as well as genes expressed preferentially at the individual stages of pollen development. Alongside updating the list of tissue-specific genes, we have investigated differentially expressed genes with respect to early expressed genes. Pollen tube growth and competition of pollen tubes in female pistil can be viewed as a race of the fittest. Accordingly, there is an apparent evolutionary trend among higher plants to store significant material reserves and nutrients during pollen maturation. This supply ensures that after pollen germination, the pollen tube utilizes its resource predominantly for its rapid elongation in the female pistil. Previous transcriptomic data from Arabidopsis showed massive expression of genes encoding proteins forming both ribosomal subunits that were accumulated in developing pollen, whereas their expression was not detectable in growing pollen tubes (Honys and Twell, 2004). We observed a similar phenomenon in less advanced bicellular tobacco pollen. Here, we describe in detail how we obtained and analyzed validated microarray dataset deposited in Gene Expression Omnibus (GSE62349).
Keywords: Tobacco; Reproduction; Male gametophyte; Pollen development transcriptome